Asuhan Kebidanan Komprehensif pada Ny. I Studi Kasus Anemia dengan Penerapan Breastfeeding Massage dan Bengkung - Nabila Ayu Ramadina; Riska Arsita Harnawati; Istiqomah Dwi Andari (Pusat Riset dan Inovasi Nasional, 2024)
WHO (World Health Organization) states that pregnant women die almost every 2 minutes in 2020, namely 6,856 people. In Indonesia, the MMR in 2023 is 4,129 people. In Central Java, the MMR in 2022 is 84.6 cases of maternal deaths per 100,000 live births with Tegal Regency at 79.9 per 100,000 per live birth. Data at the Slawi Community Health Center included 34 anemia cases out of a total of 1,015 pregnant women. Pregnant women with anemia will certainly experience various health problems. The health of pregnant women is very important because it can affect the health of the baby in their womb. Anemia is a disease that has several risk factors and bad impacts for both mother and baby. Anemia in pregnant women can increase the risk of premature birth, maternal and child death, and infectious diseases. Efforts to prevent anemia in pregnant women carried out by the government include compliance with consuming blood supplement tablets (TTD), carrying out hemoglobin checks, carrying out antenatal care checks and increasing pregnant women's knowledge about anemia. The aim of this case study is to carry out midwifery care for pregnant women, birthing mothers, postpartum mothers and newborns comprehensively using midwifery care management according to Varney and documentation using the SOAP method. The object of this case is Mrs. I G2P1A0 29 years old with normal pregnancy, delivery and postpartum. This case study was carried out in September 2023 in the Slawi Community Health Center working area. This care is described thoroughly, starting from the patient's TM III pregnancy (30 weeks to 38 weeks) and normal postpartum (6 hours postpartum to 40 days postpartum). The results processed are Comprehensive Midwifery Care for Mrs. I from 30 weeks of age, at the time of delivery until postpartum 40 days postpartum. The author concluded that the pregnancy period was normal, spontaneous delivery, BBL and postpartum were normal.